Cotadutide as an Innovative Approach to Glycemic Control and Weight Reduction in Patients with Type 2 Diabetes - A Contemporary Review - Wątek, Zuzanna; Szewczyk, Jan; Smolińska, Alicja; Krawczyk, Patrycja; Łysynkiewicz, Katarzyna; Grzyb, Izabela (Quality in Sport, 2026)
Background. Type 2 diabetes is a chronic metabolic disorder associated with impaired insulin secretion and insulin resistance, leading to persistent hyperglycemia and multiple complications. Despite advances in pharmacotherapy, many patients fail to achieve optimal metabolic control, highlighting the need for novel therapeutic approaches. Aim. The aim of this study was to present the current state of knowledge regarding cotadutide as a potential therapeutic option in the treatment of type 2 diabetes, with particular emphasis on its mechanism of action, clinical efficacy, and safety profile. Materials and methods. A narrative review of available literature was conducted, including clinical trials, meta-analyses, and preclinical studies evaluating the efficacy and safety of cotadutide in patients with type 2 diabetes and related metabolic disorders. Results. Cotadutide is a dual GLP-1 and glucagon agonist, that demonstrates a significant improvement regarding glycemia, body weight reduction and positive influence on metabolic parameters, in comparison to placebo. Clinical trials showed decrease in HbA1c, body weight and albuminuria, as well as potential benefits in liver and kidney function. The most common adverse effects involve the gastrointestinal tract. Conclusions. Cotadutide is a promising factor in diabetes type 2 treatment. It shows a broad spectrum of positive effects on metabolic parameters. However, further analysis and large-scale, long-term studies are required to establish its efficacy and safety.